Asuhan Keperawatan Pada Pasien Dengan Chronic Kidney Diseae (CKD) Diruang Rawat Inap Interne RSUP Dr. M. Djamil Padang - Nur Annisa Juliani; Aulia Asman; Mike Asmaria; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic kidney disease (CKD) is a global health problem with prevalence increasing every year. Data from the World Health Organization shows that the number of CKD sufferers in the world reaches hundreds of millions of people and is one of the diseases that contributes significantly to mortality. In 2023, CKD was ranked 9th as the biggest cause of death in the world with around 1.5 million deaths and is estimated to continue to increase until 2040. In addition, the number of patients undergoing hemodialysis therapy also continues to increase, indicating a high burden of disease and its impact on the health system and the quality of life of patients. The purpose of this study was to analyze and apply nursing care, using a case study method on one CKD patient in the Internal Inpatient Room of Dr. M. Djamil Padang General Hospital in 2026. The results of the 5-day study found nursing problems including Ineffective Airway Clearance, Ineffective Breathing Pattern, Hypervolemia, Ineffective Peripheral Perfusion, Instability of Blood Glucose Levels and Impaired Skin/Tissue Integrity. Nursing interventions and implementation included effective coughing exercises, airway management, hypervolemia management through fluid restriction and ice packs to help reduce thirst, blood transfusion, hyperglycemia management, and skin integrity maintenance. In conclusion, after nursing care, the patient's condition showed effective coughing, reduced shortness of breath, dizziness, and weakness, and edema remained. This case study is expected to be a source of information for patients and their families in understanding and managing CKD.